Abrasive and sliding wear of resin composites for dental restorations. (October 2016) - Souza, Júlio C.M.; Bentes, Ana C.; Reis, Kelly; Gavinha, Sandra; Buciumeanu, Mihaela; Henriques, Bruno; Silva, Filipe S.; Gomes, José R.
Abstract: The aim of this work was to study the abrasive and reciprocating sliding wear resistance of four commercial resin composites for dental restorations. Resin composite samples were divided into four groups considering the different materials and then separated for compressive, abrasive and sliding tests ( n =10). Micro-abrasion tests were performed against a stainless steel rotating ball on 3 N normal load for 300 revolutions in the presence of a suspension containing a commercial whitening and abrasive toothpaste. Reciprocating sliding ball-on-plate friction tests were performed against an alumina ball on 20 N normal load at 1 Hz in the presence of artificial saliva at 37 °C for 30 min. The wear volume was evaluated for the different groups of resin composites and correlated with their mechanical properties and inorganic composition in terms of size and volume percentage of filler particles. Resin composites with high volume content of inorganic fillers (82 wt%) consisting of micro particles (0.1–2.5 μm) combined with small nanoparticles (20–60 nm) revealed the most proper mechanical and tribological response. The dominant wear mechanisms consisted on fine micro-scale abrasion for abrasion tests and surface fatigue and abrasion for reciprocating sliding tests. Highlights: Micro-abrasion and wear sliding tests were performed on dental resin composites. A high volume of fillers increased the tribological response of the composites. Surface fatigue and abrasion was detected after wear sliding tests.